Philippine mining companies’ understanding of corporate social responsibility - Baquiano, Marshaley J. (Davao Research Journal: the official R & D Publication of Davao Oriental State College of Science and Technology, 2013)
This study looked at how mining companies operating in the Philippines socially represent corporate social responsibility using the lens of social representation theory. I used thematic analysis in examining nine articles taken from the websites of nine mining companies and published within the month of March, 2009. The study found shared representations of corporate social responsibility. The narratives focused on commitment to environment communities, and employees as well as working hand in hand with various stakeholders. The findings point to the need to explore the social understanding of other mining stakeholders to capture a more comprehensive picture of corporate social responsibility as this study looked only at the mining companies’ points of view. The results also show that social representations are located not only in people’s everyday talk but also in their crafted work and writings as found in mass communication media.